The IceCube Collaboration:contributions to the 30 th International Cosmic Ray Conference (ICRC 2007) - Collaboration, IceCube; Ackermann, M. (Lawrence Berkeley National Laboratory, 2007)
This paper bundles 40 contributions by the IceCube collaboration that were submitted to the 30th International Cosmic Ray Conference ICRC 2007. The articles cover studies on cosmic rays and atmospheric neutrinos, searches for non-localized, extraterrestrial {nu}{sub e}, {nu}{sub {mu}} and {nu}{sub {tau}} signals, scans for steady and intermittent neutrino point sources, searches for dark matter candidates, magnetic monopoles and other exotic particles, improvements in analysis techniques, as well as future detector extensions. The IceCube observatory will be finalized in 2011 to form a cubic-kilometer ice-Cherenkov detector at the location of the geographic South Pole. At the present state of construction, IceCube consists of 52 paired IceTop surface tanks and 22 IceCube strings with a total of 1426 Digital Optical Modules deployed at depths up to 2350 m. The observatory also integrates the 19 string AMANDA subdetector, that was completed in 2000 and extends IceCube's reach to lower energies. Before the deployment of IceTop, cosmic air showers were registered with the 30 station SPASE-2 surface array. IceCube's low noise Digital Optical Modules are very reliable, show a uniform response and record waveforms of arriving photons that are resolvable with nanosecond precision over a large dynamic range. Data acquisition, reconstruction and simulation software are running in production mode and the analyses, profiting from the improved data quality and increased overall sensitivity, are well under way.